1972
DOI: 10.1080/00071667208415981
|View full text |Cite
|
Sign up to set email alerts
|

The influence of strain and environmental factors upon feather pecking and cannibalism in fowls

Abstract: The relationship between strain, seven environmental factors and pecking damage was investigated. Strain of bird, housing system, light intensity and position effect had major influences, diet and group size had minor, while population density and brooding temperature had no appreciable effect on pecking damage. Relationships between pecking damage and social hierarchy, fear responses and body weight were also demonstrated. It is suggested that although particular "causative factors" may sometimes be of overri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
129
2
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(147 citation statements)
references
References 14 publications
15
129
2
1
Order By: Relevance
“…FP is a multifactorial problem caused by both genetic and environmental factors. There is evidence of line differences in FP (Kjaer et al 2001;Uitdehaag et al 2008), and it has been demonstrated that FP is influenced by group size, light intensity, diet and type of litter (Hughes and Duncan 1972;Blokhuis and Arkes 1984;Savory 1995). As for its aetiology, FP has been considered to be redirected ground pecking (Blokhuis 1986), abnormal dustbathing behaviour (Vestergaard and Lisborg 1993), or the consequence of a more general hyperactivity disorder (Kjaer 2009).…”
Section: Introductionmentioning
confidence: 99%
“…FP is a multifactorial problem caused by both genetic and environmental factors. There is evidence of line differences in FP (Kjaer et al 2001;Uitdehaag et al 2008), and it has been demonstrated that FP is influenced by group size, light intensity, diet and type of litter (Hughes and Duncan 1972;Blokhuis and Arkes 1984;Savory 1995). As for its aetiology, FP has been considered to be redirected ground pecking (Blokhuis 1986), abnormal dustbathing behaviour (Vestergaard and Lisborg 1993), or the consequence of a more general hyperactivity disorder (Kjaer 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Cannibalism can also occur without previous feather pecking. This is referred to as`vent-pecking' (Hughes and Duncan, 1972;Allen and Perry, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…If not controlled, this behaviour most often results in severe damage of the plumage, wounding and death (Hughes, 1982 and1985), which can result in mortality rates up to 20% and occasionally over 50%. Being a 'multi-factorial' disorder (Hughes and Duncan, 1972;Blokhuis, 1989), various causal factors relative to the rearing environment and genetic characteristics were reported (Sharma et al, 1999). Debeaking or beak trimming may reduce feather pecking but result in both acute and chronic nociceptive stimuli and potentially stress and frustration.…”
Section: Substitute the Painful Procedures By The Least Painful Proceduresmentioning
confidence: 99%